Personality Dimensions Associated with Food Addiction in a Sample of Pre-operative Bariatric Surgery Patients from Turkey - AKVARDAR, YILDIZ (SPRINGER, 2022)
Food addiction (FA) has been discussed as a potential contributing factor to the multifactorial aetiology of obesity, and an increasing number of studies have been conducted in recent years to understand this construct. Our aim was to determine the prevalence of FA in a Turkish group of pre-operative bariatric surgery patients and examine the relationship between body mass index, FA and personality traits. In this cross-sectional study, adult pre-operative bariatric surgery patients (n = 140) were evaluated for the presence of FA and related clinical factors. FA and personality traits were assessed using the Turkish versions of the Yale Food Addiction Scale (YFAS) and Temperament and Character Inventory (TCI). 47.1% of the sample was found to show signs of food addiction, as assessed by the YFAS. The mean FA symptom count of the whole sample was 3.92 +/- 1.71 out of 7. We found that participants with FA had significantly higher TCI harm avoidance scores and self-transcendence total scores than those without FA (p = 0.04, p = 0.03; respectively), whereas their self-directedness scores and resourcefulness sub-scale scores were significantly lower (p = 0.03, p < 0.01; respectively). In conclusion, lower self-directedness and higher harm avoidance are the major personality traits associated with FA in pre-operative bariatric surgery patients.
Keywords: Food addiction; Obesity; Bariatric surgery; Personality traits; Self-directedness; PROBLEMATIC EATING BEHAVIORS; OBESITY; SCALE; PREVALENCE; CANDIDATES; TRAITS; INDIVIDUALS; VALIDATION; OVERWEIGHT; DISORDER